B-type natriuretic peptide response and reverse left ventricular remodeling after surgical correction of functional mitral regurgitation in patients with advanced cardiomyopathy. Issue 4 (October 2015) - Kainuma, Satoshi; Taniguchi, Kazuhiro; Toda, Koichi; Shudo, Yasuhiro; Takeda, Koji; Funatsu, Toshihiro; Miyagawa, Shigeru; Kondoh, Haruhiko; Nishi, Hiroyuki; Yoshikawa, Yasushi; Fukushima, Satsuki; Hamada, Seiki; et al.
Abstract Background Restrictive mitral annuloplasty (RMA) can reverse left ventricular (LV) remodeling and reduce plasma B-type natriuretic peptide (BNP), a surrogate biomarker of heart failure. However, the relationship between reverse LV remodeling and plasma BNP changes after RMA is poorly defined. We explored the main hemodynamic factors contributing to change in plasma BNP after RMA in patients with functional mitral regurgitation (MR). Methods Twenty-four patients with moderate to severe functional MR secondary to LV systolic dysfunction [ejection fraction (EF) <40%] underwent 64-row multidetector computed tomography (MDCT) before and 1.4 months after RMA. LV end-diastolic volume index (EDVI), end-systolic volume index (ESVI), LVEF, and regional and global end-systolic wall stress (ESS) were calculated from 3-dimensional MDCT images, with blood samples for plasma BNP measurement collected the same day. Results After RMA, LV volumes and global ESS were decreased, while LVEF improved (all p < 0.01). There were significant correlations between changes in LVEDVI and LVESVI (r = 0.90, p < 0.0001), LVESVI and global ESS (r = 0.54, p = 0.006), and global ESS and LVEF (r = −0.60, p = 0.002). The median value for the plasma BNP also decreased from 597 pg/ml [interquartile range (IQR), 360–934 pg/ml] to 207 pg/ml (IQR, 124–271 pg/ml), in association with changes in LVEDVI (r = 0.47, p = 0.019), LVESVI (r = 0.56, p = 0.004), LVEF (r = −0.60, p = 0.002), and global ESS (r = 0.74, p < 0.0001). Multivariate regression analysis showed that global ESS change was the strongest contributor to change in natural-log-transformed plasma BNP (standardized partial regression coefficient = 0.59, p = 0.004), indicating a strong association between decrease in LV afterload and reduction in plasma BNP level after RMA. Conclusions There may be a significant association between LV reverse remodeling and plasma BNP change after RMA. Furthermore, LV end-systolic myocardial stress may be the key mechanical stimulus influencing plasma BNP after surgical correction for functional MR. Whether these favorable BNP responses and reverse remodeling can predict improved survival requires further study.